Early modern Europe : an Oxford history - Cameron, Euan (Euan K.) (Oxford University Press, 1999)
"The contributors to Early Modern Europe set out to convey the feel of the changes in life, beyond the raw historical data. Their chapters are extensively illustrated with carefully chosen images which complement the text. The book considers the evolving economy and society - the basic facts of life for the majority of Europe's people. It shows how the religious and intellectual unity of western culture fragmented and dissolved under the impact of new ideas. It examines politics, not just as the rise and fall of empires, but for the emergence of modern attitudes and techniques in governing."--Jacket